2015
DOI: 10.1111/jcmm.12529
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes transfer extracellular vesicles loaded with microRNAs to stem cells

Abstract: Telocytes (TCs) are cells ubiquitously distributed in the body and characterized by very long and thin prolongations named telopodes (Tps). Cardiac TCs are the best characterized TCs for the moment. Tps release extracellular vesicles (EVs) in vivo and in vitro suggesting that TCs regulate the activity of other cells by vesicular paracrine signals. TCs have been found within the stem cell niche of several organs. Electron microscopy or electron tomography has shown that Tps are located in close vicinity of stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 47 publications
0
77
0
2
Order By: Relevance
“…Cardiac TCs have been reported to be able to regulate cardiac stem/progenitor cells, angiogenesis, and anti-fibrosis by heterocellular junctions and secreting extracellular vesicles containing microR-NAs [24,25,[44][45][46][47][48][49][50][51]. A deeper understanding of the immunocytochemical phenotypes of cardiac TCs might help better develop cardiac TCs as a novel source for cardiac repair as preliminarily demonstrated in cardiac infarction [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac TCs have been reported to be able to regulate cardiac stem/progenitor cells, angiogenesis, and anti-fibrosis by heterocellular junctions and secreting extracellular vesicles containing microR-NAs [24,25,[44][45][46][47][48][49][50][51]. A deeper understanding of the immunocytochemical phenotypes of cardiac TCs might help better develop cardiac TCs as a novel source for cardiac repair as preliminarily demonstrated in cardiac infarction [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…). A case in point is that when TCs are transfected with microRNA‐21 mimics labelled with Cy5, the recipient cells will become Cy5 positive after incubation with the conditioned medium from TCs, indicating that vesicles are released with microRNAs from TCs . Moreover, intestinal TCs display a phagocytic‐like property termed endocytosis, which enables themselves to uptake small particles .…”
Section: Cellular Junctions Of Tcs and Their Functional Implicationsmentioning
confidence: 99%
“…Recent evidence has been found that TCs can transfer extracellular vesicles loaded with microRNAs to stem cells from the heart and blood, and this epigenetic pathway is bidirectional (Cismasiu and Popescu, 2015). In this study, some extracellular vesicles of TCs were observed by living cell imaging and TEM ( Figure S4 in Supporting Information).…”
Section: The Underlying Mechanisms By Which Tcs Promote the Proliferamentioning
confidence: 65%
“…In this study, some extracellular vesicles of TCs were observed by living cell imaging and TEM ( Figure S4 in Supporting Information). Based on previous studies, these vesicles might function as intercellular shuttles for biological signals (Cismasiu and Popescu, 2015;Manole et al, 2011). However, whether the vesicles of vascular TCs are loaded with miR-24 or other molecules requires more study.…”
Section: The Underlying Mechanisms By Which Tcs Promote the Proliferamentioning
confidence: 99%